Paraguay - Real Property Tax : Key to Fiscal Decentralization and Better Land Use, Volume 2. Technical Anneses - World Bank (Washington, DC, 2012)
This study has at its origin the land question in Paraguay, namely that land ownership is highly concentrated and has become a source of social conflict in the rural areas where one-half of the population lives. A central thesis of the study is that the existing patterns of land use and ownership, in particular, the very large land holdings (Zatifundio), are a reflection in part of the almost insignificant land tax that is charged today on rural properties. Although the property (land) tax is governed by national legislation, it is collected by the municipalities, which are constitutionally autonomous from the central government. The study thus examines municipal finances in Paraguay and estimates the revenue potential of a revised property tax. The study also reviews the economic rational for effective land taxation and the international experience in this regard. Finally, it suggests improvements in municipal financial administration that are needed in general and, in particular, to administer a revamped and more effective land tax.